Đánh giá lời giải cận tối ưu bằng phương pháp đối ngẫu với bài toán Min-Max cho hệ điều khiển nhiều đầu vào - Yen, Tran Hoang (Journal of Computer Science and Cybernetics, 2018)
It’s difficult to estimate suboptimality of minimax problems for linear systems. The estimate by dual method has proved to be effective. Here a result for  linear multi-input systems in shown.